Effects of dexamethasone on lymphocyte proliferation and cytokine production in rheumatoid arthritis - De, AntonioSergioR; Blotta, Heloisa M; Mamoni, Roney L; Louzada, Paulo; Bertolo, Manoel B; Foss, Norma T; Moreira, Ayrton C; Castro, Margaret (Journal of rheumatology, 2002)
We evaluated the pattern of dexamethasone mediated inhibition of concanavalin-A (Con-A) stimulated peripheral blood mononuclear cell (PBMC) proliferation to classify patients with rheumatoid arthritis (RA) as corticosteroid resistant (CR) or sensitive (CS). We also studied the role of T helper 1, (Th1) and Th2 cytokines in the mechanism of glucocorticoid resistance in RA. PBMC from 21 healthy controls and 15 patients with RA were isolated and cultured for the in vitro glucocorticoid sensitivity assay. Basal and Con-A stimulated PBMC proliferation levels and the inhibitory effect of different doses (10(-8), 10(-6), 10(-4) M) of dexamethasone (Dex) were evaluated. The IC50 was defined as the concentration of Dex that caused 50% inhibition of cell proliferation and subjects with an IC50 > 10(-6) M were considered to be CR. The supernatants were collected for cytokine [interleukin 4 (IL-4), IL-6, IL-10, tumor necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma)] measurement by ELISA. We observed lymphocyte proliferation after Con-A stimulation, which was inhibited by Dex in a dose-dependent manner in both groups. Two of 21 controls (9.5%) and 7/15 RA patients (53.3%) were CR (p < 0.01). Basal IL-4, IL-6, IL-10, and TNF-alpha levels were similar for both groups; however, basal IFN-gamma levels were slightly higher in patients with RA compared to controls. Con-A stimulation did not increase IL-4 or IL-6 levels compared to basal production but significantly increased IL-10 levels. IL-6 and IL-10 levels were significantly inhibited by Dex 10 M in both the control and RA groups. Con-A stimulation significantly increased TNF-alpha and IFN-gamma levels compared to the basal condition in the control and RA groups, and both cytokines were inhibited only by higher doses of Dex in the RA group. These findings might reflect a predominance of Th1 cells in RA that might contribute to corticosteroid resistance in patients in RA.